(untitled) (Research, Society and Development, 2022)
Epidermolysis Bullosa (EB), a group of rare hereditary diseases, characterized by the development of blisters in the cutaneous-mucosal region of the entire body, in response to minimal trauma, heat, or no apparent cause. birth or during the first years of life. The present study aims to review the literature on the oral manifestations found in patients with Epidermolysis Bullosa, as well as to define the dental clinical management to be followed in cases of EB. SciVerse Scopus, Scientific Electronic Library Online (Scielo), US National Library of Medicine (PUBMED) and ScienceDirect, using the Mendeley Reference Manager. In the oral cavity, an EB can manifest itself in several ways, with changes that vary in severity and quantity, depending on the type of EB, such as the formation of blisters and ulcerations (in the mucosa, palate and tongue), anodontia, junction of the vestibular sulcus (union of the attached gingiva with the oral mucosa), presence of caries and severe periodontal diseases, alveolar bone resorption and hypoplastic dental anomalies, in addition to maxillary atrophy, mandibular prognathism and mandibular course. Malocclusion is even more severe due to atresia of the alveolar arches and delay in tooth eruption. Due to the great difficulty and risk of offering dental treatment to patients with EB, the prevention of disease, biofilm and periodontal disease must be emphasized from childhood. Professionals in treatment should carry out oral hygiene and adequate prophylaxis, a diet program to prevent caries, use of gels, mouthwashes, adjuvant therapies with chlorhexidine D, cotton swabs, sprays and topical varnish applications, fluorides, biofilm scraping and leisure.